Стратегическое значение генофонда дикорастущей флоры многолетних трав для создания экологически безопасного земледелия в России - Трухан, В.А.; Козлов, Н.Н.; Коровина, В.Л. (Фактори експериментальної еволюції організмів, 2013)
Aims. In the conditions of changing climate and aggressive impact of anthropogenic factors on the environment preservation of the gene pool of wild flora of perennial grasses, as a source of selective cross-breeding of valuable genetic material, is of strategic importance for ensuring the environmentally safe agriculture in Russia. Methods. Expeditionary collection, storage, reproduction and maintenance of the collection in the laboratory and field conditions. Results. Collection of perennial grasses of All Russian Williams Fodder Research Institute has more than 6 thousand specimens of wild-growing and cultural plants. Conclusions. Collection of perennial grasses can be more efficiently used for creation of highly productive agricultural varieties and hybrids for different soil-climatic zones ofRussia.

Key words: biogeocenosis, the gene pool of wild perennial grasses, the initial breeding material, breeding program, ecology.